Prospective Study of Rape Perpetration by Young South African Men: Incidence & Risk Factors - Dunkle, Kristin (PLOS ONE, 2012)
There has been very little prospective research on rape perpetration among men. This paper describes the incidence and risk factors for new rape and attempted rape events among young South African men in an HIV prevention trial.We followed 1,147 men aged 15-26 years who enrolled into a cluster randomised controlled trial to evaluate the HIV prevention behavioural intervention Stepping Stones. Incidence rate ratios for factors associated with incident rape were derived from Poisson models.The young men reported 217 incident rapes (completed or attempted) of a girl or woman over 1,914 person years of follow up, yielding a rape incidence of 11.2 per 100 person years. Overall 24.9% of men had previously raped at baseline, and 18.9% did so during the follow up. Among the latter, 61.3% raped for the first time, and 38.7% re-offended. Multivariable Poisson modelling showed a higher incidence of rape perpetration among men who had ever used drugs (IRR 1.86 95%CI 1.39, 2.49), had eight or more lifetime partners (IRR 1.48 95% CI 1.09, 2.01), had been physically violent toward a female partner (IRR 1.50 95%CI 1.11, 2.03) and had disclosed rape perpetration at baseline (IRR 1.45 95%CI 1.07, 1.97). A lower incidence was found among those with greater resistance to peer pressure (IRR 0.85 95%CI 0.74, 0.97).The findings highlight the importance of male gender socialisation and addressing delinquent youth sub-cultures in rape prevention. Prevention requires change in hegemonic masculinity, with its emphasis on gender hierarchy, exaggerated performance of heterosexuality and control of women. Interventions are needed to address male socialisation with delinquent peers, by reducing exposure to childhood trauma and strengthening opportunities for gainful employment (in work or recreation)